International Links and the Role of the Islamic State in the Barcelona and Cambrils Attacks in 2017 - Igualada, Carlos (Perspectives on terrorism, 2021)
Barcelona and Cambrils were the latest Spanish cities hit by jihadist terrorism. The attacks that occurred on August 17 and 18, 2017 have been brought back to the spotlight with the start of the trial at the end of 2020 and the judgment published in May 2021 on the three surviving members linked to the Ripoll cell. The purpose of this article is twofold. On one hand, it addresses the purpose behind the foreign trips made by members of the terrorist group in the cell formation process and planning phase of the attacks. In order to examine this issue, this study is basing itself on the court documents and the monitoring of thirty-two sessions held in the trial related to these attacks. On the other hand, the degree of proximity between the Islamic State and the terrorist cell that perpetrated the attacks will be analyzed, with special emphasis on the evidence gathered in Alcanar and the study of the propaganda subsequently issued by the Islamic State.